Socio-Legal Approaches on City Street Vendors Management - Rina Shahriyani Shahrullah; Ampuan Situmeang; Jefri Harianto Nababan (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The Batam City Regulation Number 1 of 2019 concerning the Arrangement and Empowerment of Street Vendors (Perda PPPKL) is implemented to regulate and organize street vendors who violate the regulations to ensure the protection of the rights of every citizen, especially in Batam City. This regulation emphasizes public interests to achieve justice in the Batam community. The Public Order Agency (Satuan Polisi Pamong Praja/Satpol PP) is responsible for enforcing this regulation. However, in reality, there are still many street vendors selling in public areas. The roads in the Ramayana Jodoh area to the Tos 3000 market in Batam have turned into street vendor stalls, making it difficult for traffic to pass through. This research aims to analyze the implementation of the 2019 Batam City Regional Regulation and the enforcement of the Regulation by the Public Order Agency (Satpol PP). Therefore, it uses empirical legal research with a sociological approach. The findings of this research indicate that there are still various obstacles in implementing the Perda PPPKL by Satpol PP, including the absence of the City's Spatial Plan (RTRW) and the easy entry of second-hand goods into Batam city.